Combining ability and heterosis for some canola characteristics sown on recommended and late planting dates using biplot - Millner J; Amiri Oghan H; Shariati F; Sabaghnia N; Alizadeh B; Shirani AH; Gholamhoseini M (Biotechnical Faculty of the University of Ljubljana, 2018)
Canola (Brassica napus L.) is one of the most efficient oilproducing crops in arid and semi-arid regions of the world. In the current study, ten winter canola genotypes [seven genotypes as lines (Zarfam (L1), Talaye (L2), SLM046 (L3), Geronimo (L4), Modena (L5), Opera (L6) and Symbol (L7)] and three genotypes as testers [Okapi (T1), Licord (T2) and Orient (T3)] and their F1 hybrids (21 hybrids) were evaluated to determine the genetic parameters for grain yield, oil content, meal and seed glucosinolate contents under two different planting date [recommended (late September) and late planting (late October)]. According to combined analysis of variance there were significant differences among the genotypes for most studied traits. The genotype main effect and genotype × environment interaction (GGE) biplot method was used for analyzing line × tester design data. Among the lines, L5 showed high negative general combining ability (GCA) effect for meal glucosinolate content in both conditions whereas L1, L5 and L6 revealed high negative GCA effects for seed glucosinolate content in both planting date. From the results, it could be concluded that, hybridization between T1×L1, T1×L6 or T3×L5 is an efficient approach to release genotypes with low seed and meal glucosinolate content. Furthermore, to develop canola cultivars with higher seed and oil yield, hybridization between T1×L7 or T2×L7 is highly recommended. Improved oil content will be achieved if T1×L5, T2×L5 or T3×L6 hybrids are implemented into the breeding programs. SPOSOBNOST KOMBINIRANJA IN HETEROTIČNEGA UČINKA ZA NEKATERE LASTNOSTI OLJNE OGRŠČICE SEJANE OB PRIPOROČENEM IN POZNEM TERMINU Z UPORABO BIPLOTA Oljna ogrščica (Brassica napus L.) je v sušnih in polsušnih območjih sveta ena izmed najbolj učinkovitih poljščin za proizvodnjo olja. V raziskavi je bilo ovrednoteno deset ozimnih genotipov oljne ogrščice [sedem genotipov kot linije (Zarfam (L1), Talaye (L2), SLM046 (L3), Geronimo (L4), Modena (L5), Opera (L6) in Symbol (L7)] in trije genotipi kot testerji [Okapi (T1), Licord (T2) and Orient (T3)] ter njihovi F1 križanci (21 križancev) za določitev genetskih parametrov za pridelek zrnja, vsebnost olja, vsebnost glukozinulatov v pogači in semenu v razmerah priporočene (konec septembra) in pozne setve (konec oktobra). Glede na kombinirano analizo variance so bile med genotipi značilne razlike za večino preučevanih znakov. Za analizo glavnega učinka genotipa in njegove interakcije z okoljem pri križancih linij in testerjev je bila uporablja metoda biplota. Med linijami je L5 pokazala zelo negativno splošno kombinacijsko sposobnost (GCA) za vsebnost glukozinulatov v pogači v obeh terminih setve, v istih razmerah so imele linije L1, L5 in L6 velik negativni GCA učinek na vsebnost glukozinulatov v semenu. Iz rezultatov bi lahko zaključili, da so križanja kot so T1×L1, T1×L6 ali T3×L5 učinkovit pristop za odbor genotipov z majhno vsebnostjo glukozinulatov v semenu in pogači. Še več, za vzgojo sort oljne ogrščice z večjim pridelkom semena in olja so križanja T1×L7 ali T2×L7 zelo priporočena. Izboljšano vsebnost olja bi lahko dosegli,če bi bila križanja T1×L5, T2×L5 ali T3×L6 vključena v žlahniteljske programe.
Keywords: GGe biplot; grain yield; Heterosis; line × tester; oil content; polygon; 0703 Crop and Pasture Production